Pengaruh Work Life Balance terhadap Employee Well-Being pada Guru SLB - Shafa Arina Darmawan; Dinda Dwarawati (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Work life balance is the ability to balance the demands of one’s work and personal life. Employee well-being is a comprehensive model of subjective, workplace and psychological well-being. The purpose of this study is to see how much influence work life balance has on employee well-being on special needs teachers. The study used quantitative methods with data collection through questionnaires and multiple regression data analysis. The research population is special needs teachers in Bandung, with a sampling technique that is cluster random sampling obtained 218 sample teachers. Measuring instrument was carried out using a work life balance scale developed by Fisher et al. (2009) and adapted by Gunawan et al. (2019), then the employee well-being scale developed by Zheng et al. (2015b) and adapted by Rahmi et al. (2021). The results showed that 62% of special needs teachers had high work life balance and 69% of special needs teachers had high employee well-being. Simultaneously, work life balance affects employee well-being by 27.4%. Partially, the two dimensions of work life balance, namely personal life with interference work and personal life enhancement of work have a significant effect on employee well-being. Meanwhile, the other two dimensions, namely work interference with personal life and work enhancement of personal life, have no significant effect on employee well-being. Abstrak. Work life balance adalah kemampuan individu dalam menyeimbangkan pekerjaan dan kehidupan pribadinya. Employee well-being merupakan kesejahteraan individu pada kehidupan, pekerjaan dan psikologisnya. Penelitian ini bertujuan untuk mendapatkan data empiris mengenai pengaruh work life balance terhadap employee well-being pada guru SLB. Metode penelitian kuantitatif dengan pengumpulan data melalui kuesioner serta analisis data regresi berganda. Populasi dalam penelitian ini adalah guru SLB di Kota Bandung. Sampel sebesar 218 guru dengan teknik cluster random sampling. Alat ukur yang digunakan adalah work life balance dari Fisher et al. (2009) dan telah diadaptasi oleh Gunawan et al. (2019). Serta alat ukur employee well-being scale yang dikembangkan oleh Zheng et al. (2015b) dan telah diadaptasi oleh Rahmi et al. (2021). Hasil penelitian menunjukkan bahwa 62% guru SLB memiliki work life balance yang tinggi dan 69% guru SLB memiliki employee well-being yang tinggi. Secara simultan, work life balance berpengaruh terhadap employee well-being sebesar 27,4%. Sedangkan secara parsial, dua dimensi work life balance yaitu personal life with interference work dan personal life enhancement of work berpengaruh signifikan terhadap employee well-being. Sementara dua dimensi lainnya yaitu work interference with personal life dan work enhancement of personal life tidak berpengaruh signifikan terhadap employee well-being.